2014
DOI: 10.1093/rpd/ncu069
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of observational study of the influence of radon and other risk factors on lung cancer incidence

Abstract: An observational study is a type of epidemiological study when the researcher observes the situation but is not able to change the conditions of the experiment. The statistical analysis of the observational study of the population of Lermontov city (North Caucasus) was conducted. In the initial group, there were 121 people with lung cancer diagnosis and 196 people of the control group. Statistical analysis was performed only for men (95 cases and 76 controls). The use of logistic regression with correction on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Lung cancer is one of the most common human malignancies in the world and its mortality rate ranks first in cancer‐related causes of death . According to the histological features, lung cancer is divided into small cell lung cancer (SCLC) and non‐small cell lung cancer (NSCLC), and NSCLC accounts for approximately 80% or more . Although many novel treatment approaches have been developed for NSCLC, there are still no significant improvements in patient outcomes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung cancer is one of the most common human malignancies in the world and its mortality rate ranks first in cancer‐related causes of death . According to the histological features, lung cancer is divided into small cell lung cancer (SCLC) and non‐small cell lung cancer (NSCLC), and NSCLC accounts for approximately 80% or more . Although many novel treatment approaches have been developed for NSCLC, there are still no significant improvements in patient outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…1 According to the histological features, lung cancer is divided into small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC), and NSCLC accounts for approximately 80% or more. 2 Although many novel treatment approaches have been developed for NSCLC, there are still no significant improvements in patient outcomes. 3 Therefore, finding prognostic biomarkers is important for choosing suitable therapeutic strategies for the individual patient to acquire maximum treatment benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Pathological findings have indicated that lung cancer is a respiratory disease that may be associated with air contamination caused by industrial pollution ( 2 ). Non-small cell lung carcinoma (NSCLC) and small cell lung carcinoma are the two types of lung cancer, with incidence rates of ~85% and ~15%, respectively, according to a clinical statistical analysis of human cancers ( 3 ). NSCLCs include large-cell carcinoma, squamous cell carcinoma and adenocarcinoma, the incidences of which are increasing ( 4 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the second most common cancer among men and women: second only to prostate cancer in men, and second only to breast cancer in women (Testa et al, 2018). Non-small cell lung cancer (NSCLC) and small cell lung cancer are two types of lung cancer, and NSCLC accounts for about 85% of all lung cancer cases (Zhukovsky et al, 2014). NSCLC, including large cell carcinoma, squamous cell carcinoma, and adenocarcinoma, is associated with high incidence and mortality (Barnett et al, 2016; Brody, 2014).…”
Section: Introductionmentioning
confidence: 99%